Flexible green hydrogen: Economic benefits without increasing emissions - Oliver Ruhnau; Johanna Schiele (ZBW - Leibniz Information Centre for Economics, 2022)
Electrolytic hydrogen complements renewable energy in many net-zero energy scenarios. In these long-term scenarios with full decarbonization, the "greenness" of hydrogen is without question. In current energy systems, however, the ramp-up of hydrogen production may cause additional emissions. To avoid this potential adverse effect, recently proposed EU regulation defines strict requirements for electrolytic hydrogen to qualify as green: electrolyzers must run on additional renewable generation, which is produced in a temporally and geographically congruent manner. Focusing on the temporal dimension, this paper argues in favor of a more flexible definition of green hydrogen, which keeps the additionality criterion on a yearly basis but allows for dispatch optimization on a market basis within that period. We develop a model that optimizes dispatch and investment of a wind-hydrogen system—including wind turbines, hydrogen electrolysis, and hydrogen storage—and apply the model to a German case study based on data from 2017-2021. Contrasting different regulatory conditions, we show that a flexible definition of green hydrogen can reduce costs without additional power sector emissions. By contrast, requiring simultaneity implies that a rational investor would build a much larger wind turbine, hydrogen electrolyzer, and hydrogen storage than needed. This leads to additional costs, underutilized resources, and a potential slow-down of green hydrogen deployment. We discuss that current trends in the energy transition are likely to amplify the economic and environmental benefits of a flexible definition of green hydrogen and recommend this as the way forward for a sustainable hydrogen policy.
More recent version: http://hdl.handle.net/10419/258999
Keywords: 330